The research of hepatoprotective activity in experimental hepatitis influenced by 1,2,4-triazole derivatives - I. M. Bilay; E. O. Mihayluk; V. V. Parchenko; A. G. Kaplaushenko; A. I. Panasenko; E. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The search of new high-effective drugs is an actual problem of modern science. The purpose of our research was the pharmacological screening of 1,2,4-triazoles derivatives. Experiments have been performed on adult Wistar white rats.